Parental Involvement on Career Decision-Making among Students in Collectivist Cultures : A Systematic Literature Review on High School and Undergraduate Students in Asian Countries - Risa Ramadhany Damas; Farida Kurniawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to analyze the impact of parental involvement on career decision-making in collectivist cultures. This study employed a systematic literature review method adapted from PRISMA framework guidelines. Qualitative data collection techniques were employed, followed by thematic analysis for data interpretation. The article was searched using six online databases: Scopus, Sage Journals, SpringerLink, ProQuest, Google Scholar, and ScienceDirect. A total of 14 articles were obtained, focusing on high school and undergraduate students in Asian countries such as China, Indonesia, and South Korea. The data analysis technique for this research used a thematic analysis approach. As a result, parental involvement, through emotional support, guidance, and direct participation, significantly enhances career decision self-efficacy but may also limit autonomy due to cultural expectations. Furthermore, these results also show that students’ gender and parenting style were found to significantly influence career decision-making. The findings emphasize understanding cultural dynamics to guide educators, counselors, and policymakers in supporting students' career development. Further research is recommended to explore qualitative and mixed-method approaches to better capture the subjective and contextual experiences of students and parents in collectivist cultures. Additionally, examining comparisons between collectivist and individualist cultures could provide valuable insights into how different cultural frameworks influence career decision-making processes.